The Protective Effect of Vanadium on Cognitive Impairment and the Neuropathology of Alzheimer’s Disease in APPSwe/PS1dE9 Mice - He, Zhijun; Han, Shuangxue; Zhu, Huazhang; Hu, Xia; Li, Xiaoqian; Hou, Chaofan; Wu, Chong; Xie, Qingguo; Li, Nan; Du, Xiubo; Ni, Jiazuan; Liu, Qiong (Frontiers in Molecular Neuroscience, 2020)
Alzheimer’s disease (AD) is a widely distributed neurodegenerative disease characterized clinically by cognitive deficits and pathologically by formation of amyloid-β (Aβ) plaque and neurofibrillary tangles (NFTs) in the brain. Vanadium is a biological trace element that has a function to mimic insulin for diabetes. Bis(ethylmaltolato) oxidovanadium (IV) (BEOV) has been reported to have a hypoglycemic property, but its effect on AD remains unclear. In this study, BEOV was supplemented at doses of 0.2 and 1.0 mmol/L to the AD model mice APPSwe/PS1dE9 for 3 months. The results showed that BEOV substantially ameliorated glucose metabolic disorder as well as synaptic and behavioral deficits of the AD mice. Further investigation revealed that BEOV significantly reduced Aβ generation by increasing the expression of peroxisome proliferator-activated receptor gamma and insulin-degrading enzyme and by decreasing β-secretase 1 in the hippocampus and cortex of AD mice. BEOV also reduced tau hyperphosphorylation by inhibiting protein tyrosine phosphatase-1B and regulating the pathway of insulin receptor/insulin receptor substrate-1/protein kinase B/glycogen synthase kinase 3 beta. Furthermore, BEOV could enhance autophagolysosomal fusion and restore autophagic flux to increase the clearance of Aβ deposits and phosphorylated tau in the brains of AD mice. Collectively, the present study provides solid data for revealing the function and mechanism of BEOV on AD pathology.